PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR SISWA - Alkaromi Alkaromi (UNIB Press, 2022)
This study aims to describe the application of the Jigsaw cooperative learning model to improve cooperation and student learning achievement. This research uses Classroom Action Research (CAR) which is carried out in three cycles with four stages consisting of planning, implementing, observing, and reflecting. This study also used a quasi-experimental study. The research subjects were grade V students in the second semester of the 2020/2021 school year of SD Negeri Gugus I Merapi Timur Lahat, totaling 20 students. The research variables areThe dependent variable, which is measured is cooperation and learning achievement, then the independent variable or treatment variable applied is the application of the jigsaw model. Data collection instruments in this study used observation sheets and tests. Analysis of research data using statistical mean (mean), percentage and t-test. The results showed that there was an increase in cooperation and student learning achievement, it can be seen from the increase from cycle to cycle. the application of the type of jigsaw cooperative learning model is very effective in increasing cooperation and student achievement in grade V SD Negeri Gugus I Merapi Timur Lahat